Prevent administrative and financial corruption behaviors by activating the functions of the organizational immunity system - Abbas, Ali Abdulhassan (Journal of Economics and Administrative Sciences, 2019)
The current research aims at testing the relationship between organizational immunity and preventing administrative and financial corruption (AFC) in Iraq. The Statistical Package for the Social Sciences program (R& SPSS) was used to analyse the associated questionnaire data. The research problem has examined how to activate the functions of the organizational immune system to enable it to face organizational risks, attempt to prevent administrative and financial corruption, and access the mechanisms by which to develop organizational immunity. A sample of 161 individuals was taken who worked in the Directorate General of Education, Karbala. Also, it was concluded to a lack of memory function for organizational immunity. In addition, the influence relationships for a number of organizational immunity dimensions were weak. So, I have made several recommendations to tackle this problem. Similarly, the organization should also develop strategies to develop its organizational immunity and combat administrative and financial corruption. And then, it will be indicated to these strategies in detail at the research.